2019
DOI: 10.1002/jgc4.1189
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and opinions regarding BRCA1 and BRCA2 genetic testing among primary care physicians

Abstract: BRCA1 and BRCA2 (BRCA1/2) testing is standard for individuals with personal and/or family history suggestive of hereditary breast and ovarian cancer syndrome. The indications for testing have been expanding. To accommodate the need, incorporation of cancer genetic services into the practice of non‐genetic healthcare providers should be considered. We carried out a survey to evaluate the knowledge and opinions regarding BRCA1/2 testing among primary care providers. The survey was sent to 245 Obstetrics/Gynecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…The majority of PCPs desired additional education and resources on these topics, likely due to their reported lack of confidence. These findings add to the existing literature which indicates PCPs need further education in order to successfully integrate genetics into their clinical practice [3,[5][6][7][8][9][10]14]. It is likely that effective genomic education will need to be tailored to individual provider learning preferences and by specialty [32] and/or be made available to PCPs at the point of care.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The majority of PCPs desired additional education and resources on these topics, likely due to their reported lack of confidence. These findings add to the existing literature which indicates PCPs need further education in order to successfully integrate genetics into their clinical practice [3,[5][6][7][8][9][10]14]. It is likely that effective genomic education will need to be tailored to individual provider learning preferences and by specialty [32] and/or be made available to PCPs at the point of care.…”
Section: Discussionmentioning
confidence: 70%
“…Several of our findings are consistent with previous studies exploring PCP perspectives towards incorporating genomic medicine into their practice. Previous qualitative and quantitative studies have identified a lack of PCP confidence in their genetics knowledge as a barrier to incorporating genetics into their practices [3][4][5][6][7][8][9][10]. These studies report PCP confidence in their knowledge of various aspects of genomics to be between 15% and 50% [3][4][5][6][7]9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations